The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21091/mppa.2021.2013
|View full text |Cite
|
Sign up to set email alerts
|

Injury Frequency and Characteristics in Adolescent and Adult Circus Artists: A Pilot Prospective Cohort Study

Abstract: BACKGROUND: Despite growing participation in circus arts, little is known about associated injuries. Understanding injury patterns is critical for developing interventions to decrease injury risk and guiding rehabilitation. OBJECTIVE: The purpose of this pilot prospective cohort study was to describe injury frequency and characteristics in adolescent and adult circus artists using a surveillance method derived from dance. METHODS: Participants included 14 adolescent [mean age 14.7 yrs (1.3); 100% female] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…A recent study found clinical injury burden (injury rate plotted against injury duration) was generally higher in ground acrobats, but the exposure was not considered 7. Two studies4 12 reported higher proportions of injuries for ground acrobatics, but the exposure was also higher for these disciplines, which may have accounted for the difference. In contrast, one study showed similar 1-year injury prevalence in aerialists and non-aerialists (73% vs 81%) 6.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found clinical injury burden (injury rate plotted against injury duration) was generally higher in ground acrobats, but the exposure was not considered 7. Two studies4 12 reported higher proportions of injuries for ground acrobatics, but the exposure was also higher for these disciplines, which may have accounted for the difference. In contrast, one study showed similar 1-year injury prevalence in aerialists and non-aerialists (73% vs 81%) 6.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, calculating the time spent on each discipline within the class becomes cumbersome and prone to error. 40 Depending on the size and objectives of the study, exposure might be recorded by a single discipline or discipline subgroup ( table 6 ). Artist exposures are counted as individual sessions that may (1) be separated in time (eg, between classes or rehearsals on the same day); (2) include a separate warm-up; or (3) be a different discipline (eg, a single independent training practice that included silks and trapeze would be coded as two sessions, one of each discipline) and/or a different exposure type.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Due to the complexity of the circus arts, we recommend, in addition to hours, also recording exposure as the number of sessions for each exposure type (eg, class, independent training, physical conditioning, rehearsal or performance; table 5) by specific circus discipline 32 40. We recommend recording disciplines by session since, in circus arts, it is common to train multiple disciplines within the same session.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circus injury patterns and rates have been investigated among professional artists, [3][4][5][6] student artists [7][8][9] and adolescents. 10 Several longitudinal studies focused on the Cirque du Soleil company, 4 National Institute of Circus Arts in Australia, 7 National Center for Circus Arts in France 8 and the Montréal Circus School. 9 Although definitions of injury are inconsistent, equipment is mentioned as an external factor of injury.…”
Section: Introductionmentioning
confidence: 99%